CYP24A1 affected macrophage polarization through degradation of vitamin D as a candidate biomarker for ovarian cancer prognosis - Lin, YaoXiang; Chen, JiongFei; Xin, SiJia; Lin, Ya; Chen, YongChao; Zhou, Xiaojing; Chen, Hao; Li, XiangJuan (International immunopharmacology, 2024)
[Display omitted] •CYP24A1 regulated macrophage polarization through vitamin D (VD) degradation and served as a target gene for the second malignant subtype of OC through bioinformatics analyses.•The expression of CYP24A1 was much higher in carcinoma than in paracancerous tissue, whereas the VD content decreased in the OC cell lines with CYP24A1 overexpression.•Macrophages were polarized towards M1 after the intervention of VD-treated OC cell lines and inhibited the malignant phenotypes of OC, and the effect could be reverted by overexpressing CYP24A1, resulting in the polarization of M2 macrophages, thereby promoting tumor progression. Ovarian cancer (OC) is a fatal gynecological malignancy with a poor prognosis in which mitochondria-related genes are involved deeply. In this study, we aim to screen mitochondria-related genes that play a role in OC prognosis and investigate its effects. Through single-cell sequencing technology and bioinformatics analysis, including TCGA ovarian cancer data analysis, gene expression signature analysis (GES), immune infiltration analysis, Gene Ontology (GO) enrichment analysis, Gene Set Enrichment Analysis (GSEA), and Principal Component Analysis (PCA), our findings revealed that CYP24A1 regulated macrophage polarization through vitamin D (VD) degradation and served as a target gene for the second malignant subtype of OC through bioinformatics analyses. For further validation, the expression and function of CYP24A1 in OC cells was investigated. And the expression of CYP24A1 was much higher in carcinoma than in paracancerous tissue, whereas the VD content decreased in the OC cell lines with CYP24A1 overexpression. Moreover, macrophages were polarized towards M1 after the intervention of VD-treated OC cell lines and inhibited the malignant phenotypes of OC. However, the effect could be reversed by overexpressing CYP24A1, resulting in the polarization of M2 macrophages, thereby promoting tumor progression, as verified by constructing xenograft models in vitro. In conclusion, our findings suggested that CYP24A1 induced M2 macrophage polarization through interaction with VD, thus promoting the malignant progression of OC.